Electrochemical device and electronic device
By providing a first coating of lithium-manganese-based material or metal oxide on the surface of the positive electrode current collector of the lithium-ion battery, adaptive adjustment of the diaphragm resistance with the change of the state of charge is achieved, the problem of short circuit of the lithium-ion battery in abnormal situations is solved, and the fast charging performance and safety performance are improved.
Patent Information
- Application Number
- CN202510033897.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
In the abnormal situations such as nail penetration and impact of lithium-ion batteries, the aluminum foil positive electrode current collector is prone to short-circuit, affecting the safety of the battery. At the same time, the high-resistance coating improves safety but affects the battery performance.
A first coating layer including a lithium-rich manganese-based material or metal oxide is provided on the surface of the positive electrode current collector. By adjusting the composition and thickness of the first coating, adaptive adjustment of the diaphragm resistance with the change of the state of charge is achieved.
The fast charging performance and nail-through safety performance of the electrochemical device are improved, and the short-circuit power is avoided, while maintaining the battery's cycle life and internal resistance growth rate.
Smart Images

Figure CN119833557A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices (such as lithium-ion batteries) have become popular in our daily lives with the development of science and technology. Lithium-ion batteries have entered our daily lives along with the advancement of science and technology and the improvement of environmental protection requirements. With the widespread popularity of lithium-ion batteries, their service life has been increasingly valued by users. Consumers, after-sales service, battery manufacturers and lithium battery manufacturers have all put forward new requirements for the battery's nail penetration safety performance.
[0003] Due to abnormal conditions such as nail penetration and impact in lithium-ion batteries, aluminum foil, as a commonly used positive electrode current collector, is prone to short circuits, seriously affecting the safety of the battery. Short circuits can usually be reduced by adding a layer of coating with a higher resistivity on the surface of the aluminum foil. However, these high-resistance coatings affect battery performance to a certain extent, such as cycle life, internal resistance growth rate, and fast charging capability. Summary of the invention
[0004] The purpose of the present application is to provide an electrochemical device and an electronic device, which improve the fast charging performance of the electrochemical device while taking into account good nail penetration safety performance.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] In one embodiment of the present application, the electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive current collector, a first coating and a positive electrode material layer, the first coating is disposed on the surface of the positive current collector, and the positive electrode material layer is disposed on the surface of the first coating away from the positive current collector. The first coating includes a first main material, the first main material includes a lithium-rich manganese-based material or a metal oxide, and the mass percentage of the first main material is 20% to 95% based on the mass of the first coating; the membrane resistance of the positive electrode plate when the state of charge is greater than 80% is R1Ω, and the membrane resistance of the positive electrode plate when the state of charge is 0% to 50% is R2Ω, 100%≤(R1-R2) / R2×100%≤500%, preferably 150%≤(R1-R2) / R2×100%≤480%. When the mass percentage of the first main material and the value of (R1-R2) / R2×100% are within the above range, the positive electrode plate presents a high diaphragm resistance under a high charge state and a low diaphragm resistance under a low charge state, thereby realizing adaptive adjustment of the diaphragm resistance of the positive electrode plate as the charge state changes, which can increase the charging speed of the electrochemical device, reduce the short-circuit power, and improve the fast charging performance while taking into account good nail penetration safety performance.
[0007] In one embodiment of the present application, 0.4≤R1≤80, 0.2≤R2≤13. When the value of R1 is within the scope of the present application, the membrane resistance is higher when the state of charge of the positive electrode plate is greater than 80%, which can increase the short-circuit resistance and improve the nail penetration safety performance of the electrochemical device. When the value of R2 is within the scope of the present application, the positive electrode plate has a lower membrane resistance when the state of charge is 0% to 50%, which can increase the charging speed of the electrochemical device at a low state of charge and improve the fast charging performance of the electrochemical device.
[0008] In one embodiment of the present application, the membrane resistance of the positive electrode sheet when the state of charge is 50% to 100% is R3Ω, 0.3≤R3≤82. When the value of R3 is within the range of the present application, the membrane resistance of the positive electrode sheet when the state of charge is 50% to 100% is high, which improves the nail penetration safety performance of the electrochemical device.
[0009] In one embodiment of the present application, the lithium-rich manganese-based material includes at least one of lithium nickel cobalt manganese oxide or lithium manganese oxide. When the lithium-rich manganese-based material is selected from the materials within the above range, the positive electrode plate has a suitable membrane resistance at different charge states, which improves the fast charging performance while taking into account good nail penetration safety performance.
[0010] In one embodiment of the present application, the metal oxide includes ZnO, and the metal oxide also includes Al element; based on the mass of the metal oxide, the mass percentage of Al element is 0.6% to 4%. When the mass percentage of Al element is within the above range, the diaphragm resistance of the positive electrode sheet has a wider adjustable range, and can be adjusted to a suitable diaphragm resistance under different charge states, while improving the fast charging performance and taking into account good nail penetration safety performance.
[0011] In one embodiment of the present application, the metal oxide includes TiO2, and at least part of the surface of TiO2 is provided with a first component, the first component includes SnO2, and the first component also includes an Sb element; based on the mass of the metal oxide, the mass percentage of the first component is 44.44% to 55.25%; based on the mass of the first component, the mass percentage of the Sb element is 30.2% to 38.8%. When the mass percentage of the first component based on the metal oxide and the mass percentage of the Sb element based on the first component are within the above range, the diaphragm resistance of the positive electrode sheet has a wider adjustable range, and can be adjusted to a suitable diaphragm resistance under different charge states, while improving the fast charging performance and taking into account good nail penetration safety performance.
[0012] In one embodiment of the present application, the first coating further includes inorganic particles, the inorganic particles include at least one of nano-boehmite or aluminum oxide; based on the mass of the first coating, the mass percentage of the inorganic particles is 0% to 77%. When the mass percentage of the inorganic particles is within the above range, the fast charging performance is improved while taking into account good nail penetration safety performance.
[0013] In one embodiment of the present application, the average particle size of the first main material is 160nm to 400nm, preferably 200nm to 320nm. When the average particle size of the first main material is within the range of the present application, it can enhance the protection of the positive electrode current collector during the nail penetration test, wrap the metal burrs that may be generated by the positive electrode current collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the nail penetration safety performance of the electrochemical device.
[0014] In one embodiment of the present application, the first coating layer further includes a first binder, and the first binder includes at least one of polyvinylidene fluoride, polyacrylic acid, or polymethyl methacrylate; based on the mass of the first coating layer, the mass percentage of the first binder is 3% to 15%. When the first binder is selected from the above materials and the mass percentage is within the scope of the present application, the bonding force between the first coating layer and the positive electrode current collector can be improved, thereby improving the nail penetration safety performance of the electrochemical device.
[0015] In one embodiment of the present application, the thickness of the first coating layer is 0.2 μm to 2 μm, preferably 1 μm to 1.5 μm. When the thickness of the first coating layer is within the range of the present application, the volume energy density and nail penetration safety performance of the electrochemical device can be improved.
[0016] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has good nail penetration safety performance and fast charging performance.
[0017] Beneficial effects of this application:
[0018] The present application provides an electrochemical device and an electronic device, wherein the electrochemical device comprises a positive electrode plate, the positive electrode plate comprises a positive electrode current collector, a first coating and a positive electrode material layer, the first coating is disposed on the surface of the positive electrode current collector, and the positive electrode material layer is disposed on the surface of the first coating away from the positive electrode current collector. The first coating comprises a first main material, the first main material comprises a lithium-rich manganese-based material or a metal oxide, and the mass percentage of the first main material is 20% to 95% based on the mass of the first coating. The membrane resistance of the positive electrode plate when the state of charge is greater than 80% is R1Ω, and the membrane resistance of the positive electrode plate when the state of charge is 0% to 50% is R2Ω, 100%≤(R1-R2) / R2×100%≤500%. When the mass percentage of the first main material and the value of (R1-R2) / R2×100% are within the above range, the positive electrode plate presents a high diaphragm resistance under a high charge state and a low diaphragm resistance under a low charge state, thereby realizing adaptive adjustment of the diaphragm resistance of the positive electrode plate as the charge state changes, which can increase the charging speed of the electrochemical device, reduce the short-circuit power, and improve the fast charging performance while taking into account good nail penetration safety performance.
[0019] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0021] Figure 1 This is a schematic diagram of the structure of the positive electrode sheet in one embodiment of the present application;
[0022] Figure 2 A scatter plot showing the change in the sheet resistance of the positive electrode sheet with the state of charge in Example 1-1 of the present application;
[0023] Figure 3A scatter plot showing the change in the sheet resistance of the positive electrode sheet with the state of charge in Comparative Example 1 of the present application;
[0024] Figure 4 This is a scatter plot of the change in the membrane resistance of the positive electrode sheet with the charge state in Comparative Example 3 of the present application. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0026] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0027] In one embodiment of the present application, the electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive electrode current collector, a first coating and a positive electrode material layer, the first coating is disposed on the surface of the positive electrode current collector, and the positive electrode material layer is disposed on the surface of the first coating away from the positive electrode current collector. The first coating includes a first main material, the first main material includes a lithium-rich manganese-based material or a metal oxide, and the mass percentage of the first main material is 20% to 95% based on the mass of the first coating. The membrane resistance of the positive electrode plate when the state of charge is greater than 80% is R1Ω, and the membrane resistance of the positive electrode plate when the state of charge is 0% to 50% is R2Ω, 100%≤(R1-R2) / R2×100%≤500%, preferably 150%≤(R1-R2) / R2×100%≤480%. For example, the mass percentage of the first main material can be 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95% or a range consisting of any two of these values; the value of (R1-R2) / R2×100% can be 100%, 150%, 200%, 300%, 400%, 480%, 500% or a range consisting of any two of these values. When the mass percentage of the first main material and the value of (R1-R2) / R2×100% are within the above range, the positive electrode plate presents a high membrane resistance under a high charge state and a low membrane resistance under a low charge state, realizing the adaptive adjustment of the membrane resistance of the positive electrode plate with the change of the charge state, which can increase the charging speed of the electrochemical device, reduce the short-circuit power, and improve the fast charging performance while taking into account the good nail penetration safety performance. When (R1-R2) / R2×100% is greater than 500%, the growth rate of the diaphragm resistance of the positive electrode sheet from a low charge state to a high charge state is high, resulting in a decrease in the fast charging performance of the electrochemical device; when (R1-R2) / R2×100% is less than 100%, the growth rate of the diaphragm resistance of the positive electrode sheet from a low charge state to a high charge state is low, the short-circuit safety resistance at a high charge state is low, and the nail penetration safety performance of the electrochemical device is reduced.
[0028] In one embodiment of the present application, 0.4≤R1≤80, 0.2≤R2≤13. For example, R1 can be 0.4, 1, 10, 20, 30, 40, 50, 60, 70, 80 or a range consisting of any two of the values; R2 can be 0.2, 1, 3, 5, 7, 9, 11, 13 or a range consisting of any two of the values. When the value of R1 is within the scope of the present application, the upper limit of the membrane resistance when the state of charge of the positive electrode plate is greater than 80% is higher, which can increase the short-circuit resistance, reduce the short-circuit power, reduce the dangerous short-circuit points between the positive electrode collector and the negative electrode collector during the nail penetration test, reduce the heat power generated by the short circuit, and improve the nail penetration safety performance of the electrochemical device. When the value of R2 is within the scope of the present application, the state of charge of the positive electrode plate is 0% to 50% with a lower membrane resistance, which can increase the charging speed of the electrochemical device at a low state of charge, while improving the fast charging performance and taking into account the good nail penetration safety performance.
[0029] In one embodiment of the present application, the membrane resistance of the positive electrode sheet when the state of charge is 50% to 100% is R3Ω, 0.3≤R3≤82. For example, R3 can be 0.3, 1, 10, 20, 30, 40, 50, 60, 70, 80, 82 or a range consisting of any two of these values. When the value of R3 is within the range of the present application, the membrane resistance of the positive electrode sheet when the state of charge is 50% to 100% is high, which can increase the short-circuit resistance, reduce the short-circuit power, reduce the dangerous short-circuit points between the positive current collector and the negative current collector during the nail penetration test, reduce the heat power generated by the short circuit, and improve the nail penetration safety performance of the electrochemical device.
[0030] In this application, the above-mentioned “the first coating is disposed on the surface of the positive electrode current collector” means that the first coating can be disposed on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the “surface” here can be the entire area of the positive electrode current collector, or it can be a partial area of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. Specifically, if Figure 1 As shown, a first coating layer 12 and a positive electrode material layer 13 are sequentially stacked on the two surfaces of the positive electrode current collector 11. The above-mentioned "the positive electrode material layer is arranged on the surface of the first coating layer away from the positive electrode current collector" can be understood by analogy.
[0031] In one embodiment of the present application, the lithium-rich manganese-based material includes at least one of lithium nickel cobalt manganese oxide or lithium manganese oxide (LiMnO2). For example, lithium nickel cobalt manganese oxide may include but is not limited to LiNi 0.33 Co 0.33 Mn 0.33 O2、LiNi 0.5 Co 0.2Mn 0.3 O2、LiNi 0.6 Co 0.1 Mn 0.3 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 or LiNi 0.9 Co 0.05 Mn 0.05 At least one of O2. When the lithium-rich manganese-based material is selected from the materials within the above range, the positive electrode sheet has a suitable membrane resistance at different charge states, thereby improving the nail penetration safety performance and fast charging performance of the electrochemical device.
[0032] In one embodiment of the present application, the metal oxide includes ZnO, and the metal oxide also includes Al element; based on the mass of the metal oxide, the mass percentage of the Al element is 0.6% to 4%. For example, based on the mass of the metal oxide, the mass percentage of the Al element can be 0.6%, 1%, 1.5%, 2%, 3%, 4% or a range consisting of any two of these values. When the mass percentage of the Al element is within the above range, the diaphragm resistance of the positive electrode sheet has a wider adjustable range, and can be adjusted to a suitable diaphragm resistance under different charge states, while improving the fast charging performance and taking into account good nail penetration safety performance.
[0033] In one embodiment of the present application, the metal oxide includes TiO2, at least part of the surface of TiO2 is provided with a first component, the first component includes SnO2, and the first component also includes Sb element; based on the mass of the metal oxide, the mass percentage of the first component is 44.44% to 55.25%; based on the mass of the first component, the mass percentage of the Sb element is 30.2% to 38.8%. For example, based on the mass of the metal oxide, the mass percentage of the first component can be 44.44%, 45%, 47%, 49%, 51%, 53%, 55%, 55.25%, or a range consisting of any two of the values; based on the mass of the first component, the mass percentage of the Sb element can be 30.2%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 38.8%, or a range consisting of any two of the values. When the mass percentage of the first component based on the metal oxide and the mass percentage of the Sb element based on the first component are within the above range, the diaphragm resistance of the positive electrode sheet has a wider adjustable range, and can be adjusted to a suitable diaphragm resistance under different charge states, thereby improving the fast charging performance while taking into account good nail penetration safety performance.
[0034] In one embodiment of the present application, the first coating also includes inorganic particles, and the inorganic particles include at least one of nanoboehmite or aluminum oxide; based on the mass of the first coating, the mass percentage of the inorganic particles is 0% to 77%. For example, the mass percentage of the inorganic particles can be 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 77% or a range consisting of any two of the values. When the mass percentage of the inorganic particles is within the above range, the conductivity of the inorganic particles is low, and the introduction of the first coating can further improve the diaphragm resistance of the positive electrode sheet in a high charge state, and realize the adaptive adjustment of the diaphragm resistance of the positive electrode sheet with a wider adjustable range as the charge state changes, while improving the fast charging performance and taking into account the good nail penetration safety performance.
[0035] In one embodiment of the present application, the average particle size of the first main material is 160nm to 400nm, preferably 200nm to 320nm. For example, the average particle size of the first main material can be 160nm, 200nm, 250nm, 320nm, 350nm, 400nm or a range consisting of any two of these values. When the average particle size of the first main material is within the scope of the present application, the first main material with a nanometer particle size can increase the packing density between particles, form a denser first coating on the surface of the positive current collector, increase the crush resistance of the first coating, enhance the protection of the positive current collector during the nail penetration test, wrap the metal burrs that may be generated by the positive current collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the nail penetration safety performance of the electrochemical device.
[0036] In one embodiment of the present application, the first coating layer further includes a first binder, and the first binder includes at least one of polyvinylidene fluoride, polyacrylic acid or polymethyl methacrylate; based on the mass of the first coating layer, the mass percentage of the first binder is 3% to 15%. For example, the mass percentage of the first binder can be 3%, 5%, 7%, 9%, 11%, 15% or a range consisting of any two of the values. When the first binder is selected from the above materials and the mass percentage is within the scope of the present application, the overall adhesion of the first coating layer can be improved, and the adhesion between the first coating layer and the positive electrode current collector can be improved, thereby improving the nail penetration safety performance of the electrochemical device.
[0037] In one embodiment of the present application, the thickness of the first coating is 0.2 μm to 2 μm, preferably 1 μm to 1.5 μm. For example, the thickness of the first coating can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.25 μm, 1.5 μm, 2 μm or a range consisting of any two of the values. When the thickness of the first coating is within the scope of the present application, the first coating has a high mechanical strength, can protect the positive electrode collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the nail penetration safety performance of the electrochemical device; at the same time, the thinner first coating can also increase the volume energy density of the electrochemical device.
[0038] The present application has no particular restrictions on the preparation method of the metal oxide, as long as the purpose of the present application can be achieved. For example, the preparation method of the metal oxide may include but is not limited to the following steps:
[0039] (1) ZnO and an aluminum-containing compound in a mass ratio of 99:1 to 94:6 are ground and mixed, and then calcined at 500°C to 700°C for 2 to 3 hours to obtain Al-doped ZnO powder. Alternatively, ZnO and an aluminum-containing compound in a mass ratio of 99:1 to 94:6 are dissolved in water, and ammonia water is added as a precipitant, and stirred to precipitate. Then, Al-doped ZnO powder is formed by filtering, drying, and calcining at 500°C to 700°C.
[0040] (2) Take a tin-containing compound and an antimony-containing compound in a mass ratio of 62:38 to 48:52 to obtain a mixture, then take the mixture and TiO2 in a mass ratio of 1:1 to 7:3, and dissolve the mixture in ethanol to obtain a sol precursor solution. Use ultrasonic dispersion to disperse TiO2 particles in the sol precursor solution, and adjust the pH of the solution by adding an appropriate amount of water or ammonia water to hydrolyze the tin-containing compound and the antimony-containing compound on the surface of TiO2 and gradually form a gel mixture. After drying the TiO2 particles containing the gel mixture on the surface, calcine at 400°C to 700°C to finally form a TiO2 material with antimony-doped SnO2 on the surface.
[0041] The above-mentioned aluminum-containing compounds may include but are not limited to at least one of Al2O3 or Al(NO3)3; the above-mentioned antimony-containing compounds may include but are not limited to at least one of Sb2O3 or SbCl3; the above-mentioned tin-containing compounds may include but are not limited to SnCl4.
[0042] The present application has no particular restrictions on the method for regulating the average particle size of the first main material, as long as the purpose of the present application can be achieved. For example, the average particle size of the first main material can be regulated by regulating the grinding time and the grinding speed. Exemplarily, when other conditions remain unchanged, the average particle size of the first main material decreases when the grinding time is extended; and the average particle size of the first main material increases when the grinding time is shortened.
[0043] The present application has no particular restrictions on the method for regulating the mass percentage of the Al element based on the metal oxide, as long as the purpose of the present application can be achieved. For example, the mass ratio of ZnO and the aluminum-containing compound can be regulated. When the mass ratio of ZnO and the aluminum-containing compound increases, the mass percentage of the Al element based on the metal oxide decreases; when the mass ratio of ZnO and the aluminum-containing compound decreases, the mass percentage of the Al element based on the metal oxide increases.
[0044] The present application has no particular restrictions on the method for regulating the mass percentage of the first component based on the metal oxide, as long as the purpose of the present application can be achieved. For example, it can be regulated by the mass ratio of the sol precursor solution and TiO2. When the mass ratio of the sol precursor solution and TiO2 increases, the mass percentage of the first component based on the metal oxide increases; when the mass ratio of the sol precursor solution and TiO2 decreases, the mass percentage of the first component based on the metal oxide decreases.
[0045] The present application has no particular restrictions on the method for regulating the mass percentage of the Sb element based on the first component, as long as the purpose of the present application can be achieved. For example, the mass ratio of the tin-containing compound and the antimony-containing compound can be regulated. When the mass ratio of the tin-containing compound to the antimony-containing compound increases, the mass percentage of the Sb element based on the metal oxide decreases; when the mass ratio of the tin-containing compound to the antimony-containing compound decreases, the mass percentage of the Sb element based on the metal oxide increases.
[0046] The present application has no special restrictions on the method for regulating the values of R1 and R2, as long as the purpose of the present application can be achieved. In the present application, the values of R1 and R2 will be affected by multiple preparation parameters in the preparation process of the positive electrode plate, and will change with the changes in these preparation parameters, such as the type and mass percentage of the first main material, the type and mass percentage of the first binder, the type and mass percentage of the inorganic particles, the thickness of the first coating, the mass percentage of the Al element based on the metal oxide, the mass percentage of the Sb element based on the first component, etc., as long as R1 and R2 satisfy 100%≤(R1-R2) / R2×100%≤500%.
[0047] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet may include but is not limited to the following steps: the first main material, the inorganic particles and the first binder are mixed in a mass ratio of (20 to 95): (0 to 77): (3 to 15), deionized water is added as a solvent, and stirred evenly to obtain a first coating slurry with a solid content of 70wt% to 80wt%. Then the first coating slurry is coated on one surface of the positive electrode current collector of 5μm to 20μm, and the first coating with a thickness of 0.2μm to 2μm is obtained after baking at 90℃ to 180℃ for 1h to 3h. Then prepare the positive electrode material layer slurry, apply the positive electrode material layer slurry on the surface of the first coating, dry it, and obtain a positive electrode sheet with a single-sided coating of the first coating and the positive electrode material layer. Repeat the above steps on the other surface of the positive electrode current collector to obtain a positive electrode sheet with a double-sided coating of the first coating and the positive electrode material layer.
[0048] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0049] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to at least one of lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0050] The positive electrode material layer may also include a conductive agent and a second binder. The present application does not particularly limit the types of the conductive agent and the second binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the second binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the second binder in the positive electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0051] The present application has no particular restrictions on the thickness of the positive electrode current collector and the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode material layer can be 70 μm to 90 μm, and the thickness of the positive electrode current collector can be 5 μm to 20 μm.
[0052] In the present application, the electrochemical device also includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0053] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector or a titanium-copper composite current collector, etc.
[0054] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.
[0055] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent and a second binder, for example, at least one of the conductive agent and the second binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, and the second binder in the negative electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0056] The present application has no particular limitation on the thickness of the negative electrode material layer and the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 80 μm to 100 μm, and the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0057] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a second binder. The present application has no particular restrictions on the conductive agent and the second binder in the conductive layer, which may be, for example, the above conductive agent and the above second binder.
[0058] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) membranes), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0059] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0060] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0061] In some embodiments of the present application, the inorganic layer includes ceramic particles and a second binder. The present application has no particular restrictions on ceramic particles, such as ceramic particles may include at least one of silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the second binder, such as the second binder may be at least one of the above-mentioned second binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0062] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0063] In the present application, the electrochemical device further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0064] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.
[0065] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0066] The carbonate compound may include but is not limited to at least one of a chain carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The chain carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0067] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0068] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0069] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has good nail penetration safety performance and fast charging performance.
[0070] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0071] Example
[0072] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0073] Test methods and equipment:
[0074] The average particle size test of the first main material
[0075] The lithium-ion battery is disassembled to obtain the positive electrode sheet, and the positive electrode sheet is plasma cut longitudinally along the thickness direction, and polished by argon ion polishing technology to obtain a flat cross section, and then a scanning electron microscope (OXFORD·EDS) is used to take SEM photos at a magnification of 50,000 times to observe the first main material particles. Then, 30 particles are randomly selected from the SEM photos using image analysis software, and the area of each of these particles is calculated. Then, assuming that the particles are spherical, the particle size D (diameter) of each particle is calculated by the following formula: D=2×(S1 / π)1 / 2; wherein S1 is the area of the particle; and the particle sizes of the 30 particles obtained are averaged, which is the average particle size of the first main material.
[0076] First coating thickness test
[0077] The lithium-ion battery was disassembled to obtain the positive electrode sheet, and the positive electrode sheet was plasma cut longitudinally along the thickness direction and polished by argon ion polishing technology to obtain a flat cross section. Then, a scanning electron microscope (OXFORD·EDS) was used to observe and measure the thickness of the first coating at three locations at a magnification of 50,000 times, and the average value was taken as the thickness of the first coating.
[0078] Nail penetration test
[0079] Take 10 lithium-ion batteries in the embodiment or comparative example and fully charge them at 25±3°C. The specific steps are: charge at a constant current of 0.5C to 4.5V, and then charge at a constant voltage of 4.5V to a current cutoff of 0.05C.
[0080] The nail penetration test was conducted on lithium-ion batteries at 25±3℃, using a steel nail with a diameter of 4mm, made of carbon steel, with a taper of 16.5mm, and a total length of 100mm. The nail penetration speed was set to 30mm / s, and the nail penetration depth was based on the taper of the steel nail passing through the lithium-ion battery. The state of the lithium-ion battery was observed during the test, and the judgment standard was whether the lithium-ion battery burned or exploded. The pass rate of the nail penetration test = the number of lithium-ion batteries that did not burn or explode during the nail penetration test / 10×100%.
[0081] Fast charging performance test
[0082] The fast charging performance of lithium-ion batteries is evaluated by the charging time of lithium-ion batteries. The longer the charging time, the worse the fast charging performance, and the shorter the charging time, the better the fast charging performance.
[0083] The test process is as follows: discharge the lithium-ion battery at a constant current of 0.2C to 3.0V, at which time the lithium-ion battery is in a fully discharged state; place the fully discharged lithium-ion battery in a 25°C constant temperature box, and after standing for 30 minutes, charge the lithium-ion battery at a constant current of 3C to 4.5V, and then charge it at a constant voltage of 4.5V to 0.05C, at which time the lithium-ion battery is in a fully charged state; record the charging time t1 of the lithium-ion battery from full discharge to full charge, in seconds.
[0084] Diaphragm resistance test
[0085] First, fully charge the lithium-ion battery at the rated voltage: the specific steps are to charge it to 4.5V at a constant current of 0.5C, and then charge it at a constant voltage of 4.5V until the current is cut off at 0.05C. Then discharge it at a rate of 0.1C for t hours to obtain the lithium-ion battery at the target state of charge: t=[(100%-target SOC) / 10%]. The positive electrode sheet is obtained by disassembling the lithium-ion battery after discharging it to different states of charge. After wiping off the surface electrolyte and attached substances, the part of the positive electrode current collector surface coated with the first coating and the positive electrode material layer is cut into a test sample with a size of 60mm×80mm. Using a film resistance meter, the test pressure is 0.4T, the pressure holding time is 10s, and the test area is 154mm 2 The membrane resistance of the positive electrode sheet at different charge states in each embodiment is obtained by testing. The membrane resistance of the positive electrode sheet with a charge state of 100% is recorded as R1, the membrane resistance of the positive electrode sheet with a charge state of 0% is recorded as R2, and the membrane resistance of the positive electrode sheet with a charge state of 50% is recorded as R3. The membrane resistance of the positive electrode sheet at different charge states in each embodiment is obtained by testing. The lithium-ion battery obtained by the lithium-ion battery preparation method of Example 1-1, Comparative Example 1 and Comparative Example 2 is disassembled at different charge states, and the membrane resistance of the positive electrode sheet is measured to obtain Figure 2 , Figure 3 and Figure 4 .
[0086] Mass percentage test of Al element, Sb element and the first component
[0087] (1) After the lithium-ion battery was discharged to 3V at 0.2C, the positive electrode sheet was removed and cut into 10 small discs with a diameter of 16 mm. After the positive electrode material layer was scraped off with a knife, the first coating was scraped off from the positive electrode current collector of a single small disc to obtain the first coating powder. 0.2 g of the first coating powder was weighed and digested with 10 mL of aqua regia, and diluted to a constant volume of 100 mL with deionized water in a volumetric flask. Then, an inductively coupled plasma analyzer (ICP, model AVIO-200) was used to set the radio frequency generator (R F) The frequency is 40.68MHz, the secondary pressure of argon is 0.6MPa, the RF power is 1400W, and the pump speed is 1.0mL / min. The content of Al, Zn, Sn, Sb and Ti in the first coating of a single small disc is tested. The content of Al, Zn, Sn, Sb and Ti obtained from the above 10 small discs is averaged to obtain the mass percentage of Al, Zn, Sn, Sb and Ti in the first coating. Among them, aqua regia is obtained by mixing concentrated nitric acid and concentrated hydrochloric acid in a volume ratio of 1:1.
[0088] (2) The mass percentage of Sn in the first coating is converted to the mass percentage of SnO2 W1, the mass percentage of Sb is recorded as W2, the mass percentage of Sb is converted to the mass percentage of Sb2O5 W3, and the mass percentage of Ti is converted to the mass percentage of TiO2 W4. The mass percentage of the first component based on the metal oxide = (W1+W3) / (W1+W3+W4)×100%, the mass percentage of Sb based on the first component W Sb =W2 / (W1+W3)×100%.
[0089] (3) The mass percentage of Zn in the first coating is converted to the mass percentage of ZnO W5, the mass percentage of Al is recorded as W6, and the mass percentage of Al is converted to the mass percentage of Al2O3 W7. The mass percentage of Al based on metal oxide W Al =W6 / (W5+W7)×100%.
[0090] Example 1-1
[0091] <Preparation of the first main material>
[0092] (1) Take a tin-containing compound SnCl4 and an antimony-containing compound SbCl3 in a mass ratio of 55:45 to obtain a mixture, then take the mixture in a mass ratio of 5:3 and TiO2, dissolve the mixture in ethanol to obtain a sol precursor solution. Use ultrasonic dispersion to disperse TiO2 particles in the sol precursor solution, and adjust the pH of the solution by adding ammonia water. When the pH of the solution reaches 5, the tin-containing compound SnCl4 and the antimony-containing compound SbCl3 are hydrolyzed on the surface of TiO2 and gradually form a gel mixture. After drying, the TiO2 particles containing the gel mixture on the surface are calcined at 500°C to finally form a TiO2 material with antimony-doped SnO2 on the surface. Among them, the mass percentage of the first component based on the metal oxide is 50%, the mass percentage of the Sb element based on the first component is 36%, and the average particle size of the first main material is 260nm.
[0093] <Preparation of positive electrode sheet>
[0094] The first main material and the first binder polyacrylic acid prepared above were mixed in a mass ratio of 91:9, deionized water was added as a solvent, and the mixture was stirred evenly to obtain a first coating slurry with a solid content of 75wt%, which was coated on one surface of the 8μm positive electrode current collector aluminum foil, and dried at 120°C to obtain a first coating with a thickness of 1.25μm. The positive electrode active material lithium cobalt oxide, the conductive agent carbon nanotube (CNT), and the second binder polyvinylidene fluoride were mixed in a mass ratio of 97.3:1.1:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry was evenly coated on the surface of the first coating, and dried at 120°C to obtain a positive electrode sheet with a single-sided coating of the first coating and the positive electrode material layer, and the coating weight of the positive electrode active layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil, and after drying at 120°C, a positive electrode sheet coated with the first coating and the positive electrode material layer on both sides is obtained. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 90μm.
[0095] The schematic diagram of the structure of the positive electrode sheet prepared in Example 1-1 is as follows Figure 1 shown.
[0096] <Preparation of negative electrode sheet>
[0097] The negative electrode active material artificial graphite, the second binder styrene butadiene rubber (SBR) and the second binder carboxymethyl cellulose (CMC) were mixed at a mass ratio of 97.7:1:1.3, and then deionized water was added as a solvent to prepare a slurry with a solid content of 70wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. The thickness of the single-sided negative electrode material layer is 85μm.
[0098] <Preparation of Electrolyte>
[0099] In an argon atmosphere glove box with a water content of less than 10ppm, carbonate compounds ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of 10:30:60 to obtain a basic solvent, and lithium salt LiPF6 was added and stirred evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the remainder is the basic solvent.
[0100] <Isolation film>
[0101] A polyethylene porous polymer film with a thickness of 8 μm (manufacturer: Celgard Membrane Co., Ltd., USA) was used as a separator.
[0102] <Preparation of lithium-ion batteries>
[0103] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound, and the electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, and shaping processes, a lithium-ion battery is obtained. The upper limit voltage of the formation is 4.53V, the formation temperature is 85°C, and the formation time is 50min.
[0104] Example 1-2 to Example 1-7
[0105] Except for adding alumina as inorganic particles in <Preparation of Positive Electrode Plate> and adjusting the mass percentage of the first main material, the mass percentage of inorganic particles and the mass percentage of the first binder according to Table 1, the rest is the same as Example 1-1.
[0106] Example 1-8 to Example 1-13
[0107] Except for adjusting the mass ratio of the sol precursor solution and TiO2 and the mass ratio of the tin-containing compound and the antimony-containing compound in <Preparation of the Positive Electrode Plate> so that the mass percentage of the first component and the mass percentage of the Sb element are as shown in Table 1, the rest is the same as Example 1-1.
[0108] Example 1-14 to Example 1-23
[0109] Except for adjusting the average particle size of the first main material and the thickness of the first coating layer according to Table 1 in <Preparation of Positive Electrode Sheet>, the rest is the same as Example 1-1.
[0110] Examples 1-24
[0111] Except that in the diaphragm resistance test, the diaphragm resistance of the positive electrode sheet with a charge state of 90% is recorded as R1, the diaphragm resistance of the positive electrode sheet with a charge state of 20% is recorded as R2, and the diaphragm resistance of the positive electrode sheet with a charge state of 60% is recorded as R3, the rest is the same as Example 1-1.
[0112] Examples 1-25
[0113] Except that the type of the first binder in <Preparation of Positive Electrode Sheet> is replaced with polyvinylidene fluoride, the rest is the same as Example 1-1.
[0114] Examples 1-26
[0115] Except that the type of inorganic particles in <Preparation of positive electrode sheet> is replaced with nano-boehmite, the rest is the same as Example 1-6.
[0116] Examples 1-27
[0117] Except that <Preparation of the first main material> is replaced by the following preparation process, the rest is the same as Example 1-1.
[0118] <Preparation of the first main material>
[0119] ZnO and aluminum-containing compound Al2O3 in a mass ratio of 94:6 were taken, ground and mixed, and then calcined at 600°C for 3 hours to obtain Al-doped ZnO powder.
[0120] Example 1-28 to Example 1-31
[0121] Except for adjusting the mass ratio of ZnO and the aluminum-containing compound in <Preparation of Positive Electrode Plate> so that the mass percentage of Al element is as shown in Table 1, the rest is the same as Example 1-27.
[0122] Example 2-1
[0123] <Preparation of positive electrode sheet>
[0124] The first main material, lithium-rich manganese-based material LiMnO2, and the first binder, polyacrylic acid, were mixed in a mass ratio of 91:9, deionized water was added as a solvent, and the mixture was stirred evenly to obtain a first coating slurry with a solid content of 75wt%, which was coated on one surface of an 8μm positive electrode current collector aluminum foil, and dried at 120°C to obtain a first coating with a thickness of 1.25μm. The positive electrode active material, lithium cobalt oxide, the conductive agent carbon nanotube (CNT), and the second binder polyvinylidene fluoride were mixed in a mass ratio of 97.3:1.1:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry was evenly coated on the surface of the first coating, and dried at 120°C to obtain a positive electrode sheet with a single-sided coating of the first coating and the positive electrode material layer, and the coating weight of the positive electrode active layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil, and after drying at 120°C, a positive electrode sheet with a first coating and a positive electrode material layer on both sides is obtained. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the average particle size of the first main material is 260nm, and the thickness of the single-sided positive electrode material layer is 90μm.
[0125] <Preparation of negative electrode sheet>
[0126] The negative electrode active material artificial graphite, the second binder styrene butadiene rubber (SBR) and the second binder carboxymethyl cellulose (CMC) were mixed at a mass ratio of 97.7:1:1.3, and then deionized water was added as a solvent to prepare a slurry with a solid content of 70wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. The thickness of the single-sided negative electrode material layer is 85μm.
[0127] <Preparation of Electrolyte>
[0128] In an argon atmosphere glove box with a water content of less than 10ppm, carbonate compounds ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of 10:30:60 to obtain a basic solvent, and lithium salt LiPF6 was added and stirred evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the remainder is the basic solvent.
[0129] <Isolation film>
[0130] A polyethylene porous polymer film with a thickness of 8 μm (manufacturer: Celgard Membrane Co., Ltd., USA) was used as a separator.
[0131] <Preparation of lithium-ion batteries>
[0132] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound, and the electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, and shaping processes, a lithium-ion battery is obtained. The upper limit voltage of the formation is 4.53V, the formation temperature is 85°C, and the formation time is 50min.
[0133] Example 2-2 to Example 2-4
[0134] Except for adjusting the mass percentage of the first main material, the mass percentage of the inorganic particles and the mass percentage of the first binder in <Preparation of the Positive Electrode Sheet> according to Table 2, the rest is the same as Example 2-1.
[0135] Example 2-5 to Example 2-6
[0136] Except for adjusting the type of lithium-rich manganese-based material according to Table 2 in <Preparation of positive electrode sheet>, the rest is the same as Example 2-1.
[0137] Comparative Example 1
[0138] Except that the first coating layer is not provided on the surface of the positive electrode current collector, the rest is the same as Example 1-1.
[0139] Comparative Examples 2 to 6
[0140] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0141] Comparative Example 7 to Comparative Example 8
[0142] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 2-1.
[0143] The data of each embodiment and comparative example are shown in Table 1 and Table 2.
[0144] Table 1
[0145] Note: “ / ” in Table 1 means that there is no corresponding preparation parameter or substance. Al Indicates the mass percentage of Al element based on metal oxide, W Sb represents the mass percentage of the Sb element based on the first component, and t1 represents the charging time of the lithium-ion battery from full discharge to full charge.
[0146] From Example 1-1 to Example 1-31, it can be seen from Comparative Examples 1 to Comparative Examples 6 that when the positive electrode plate has the structure of the first coating of the present application and the mass percentage of the first main material, the values of R1 and R2, the value of (R1-R2) / R2×100%, the mass percentage of the inorganic particles and the mass percentage of the first binder are within the scope of the present application, the obtained lithium-ion battery has a shorter charging time from full discharge to full charge and a higher pass rate of the nail penetration test, which indicates that the lithium-ion battery of the present application has taken into account good nail penetration safety performance while improving the fast charging performance. The positive electrode plate in Comparative Example 1 does not have the first coating structure of the present application, and the mass percentage of the first main material and / or the value of (R1-R2) / R2×100% in Comparative Examples 2 to Comparative Examples 6 are not within the scope of the present application. The obtained lithium-ion battery has a longer charging time from full discharge to full charge and / or a lower pass rate of the nail penetration test, which cannot take into account good fast charging performance and nail penetration safety performance.
[0147] from Figure 2 It can be seen that when the positive electrode sheet of Example 1-1 has the structure of the first coating layer of the present application and the mass percentage of the first main material, the value of (R1-R2) / R2×100%, the mass percentage of the inorganic particles and the mass percentage of the first binder are within the range of the present application, the positive electrode sheet exhibits a high membrane resistance in a high charge state and a low membrane resistance in a low charge state, thereby achieving adaptive adjustment of the membrane resistance of the positive electrode sheet as the charge state changes. Figure 3 and Figure 4 It can be seen that the positive electrode plate of comparative example 1 does not have the first coating structure of the present application, the mass percentage of the first main material, the value of (R1-R2) / R2×100%, the mass percentage of the inorganic particles and the mass percentage of the first binder in the positive electrode plate of comparative example 3 are not within the scope of the present application, and there is no obvious change trend in the diaphragm resistance of the positive electrode plate under different charge states, and it is impossible to achieve adaptive adjustment of the diaphragm resistance of the positive electrode plate as the charge state changes.
[0148] The mass percentage of the first component and the mass percentage of the Sb element usually affect the fast charging performance and nail penetration safety performance of the lithium-ion battery. It can be seen from Examples 1-1 and 1-8 to 1-13 that when the mass percentage of the first component and the mass percentage of the Sb element are within the range of this application, the obtained lithium-ion battery has a shorter charging time from full discharge to full charge, and a higher pass rate for the nail penetration test, which shows that the lithium-ion battery of this application has improved fast charging performance while taking into account good nail penetration safety performance.
[0149] The average particle size of the first main material and the thickness of the first coating usually affect the fast charging performance and nail penetration safety performance of the lithium-ion battery. It can be seen from Examples 1-1 and 1-14 to 1-23 that when the average particle size of the first main material and the thickness of the first coating are within the range of this application, the obtained lithium-ion battery has a shorter charging time from full discharge to full charge, and a higher pass rate for the nail penetration test, which shows that the lithium-ion battery of this application has improved fast charging performance while taking into account good nail penetration safety performance.
[0150] The type of inorganic particles and the type of the first binder usually affect the fast charging performance and nail penetration safety performance of the lithium-ion battery. It can be seen from Example 1-1 and Example 1-25 to Example 1-26 that when the type of inorganic particles and the type of the first binder are within the scope of this application, the obtained lithium-ion battery has a shorter charging time from full discharge to full charge, and a higher pass rate for the nail penetration test, which shows that the lithium-ion battery of this application has improved fast charging performance while taking into account good nail penetration safety performance.
[0151] The type of metal oxide and the mass percentage of the Al element usually affect the fast charging performance and nail penetration safety performance of lithium-ion batteries. It can be seen from Examples 1-1 and 1-27 to 1-31 that when the mass percentage of the Al element is within the range of this application, the obtained lithium-ion battery has a shorter charging time from full discharge to full charge, and a higher pass rate for the nail penetration test, which shows that the lithium-ion battery of this application has improved fast charging performance while taking into account good nail penetration safety performance.
[0152] Table 2
[0153] Note: “ / ” in Table 2 indicates that there is no corresponding preparation parameter or substance, and t1 indicates the charging time of a lithium-ion battery from full discharge to full charge.
[0154] From Example 2-1 to Example 2-6, Comparative Examples 7 to Comparative Examples 8, it can be seen that when the positive electrode sheet has the structure of the first coating of the present application and the mass percentage of the first main material, the value of (R1-R2) / R2×100%, the mass percentage of the inorganic particles, and the mass percentage of the first binder are within the scope of the present application, the obtained lithium-ion battery has a shorter charging time from full discharge to full charge, and a higher pass rate of the nail penetration test, which indicates that the lithium-ion battery of the present application has improved fast charging performance while taking into account good nail penetration safety performance. The mass percentage of the first main material in Comparative Examples 7 to Comparative Examples 8 is not within the scope of the present application, and the obtained lithium-ion battery has a longer charging time from full discharge to full charge or a lower pass rate of the nail penetration test, which cannot take into account good fast charging performance and nail penetration safety performance.
[0155] The type of lithium-rich manganese-based material usually affects the fast charging performance and nail penetration safety performance of lithium-ion batteries. It can be seen from Examples 2-1 and 2-5 to 2-6 that when the type of lithium-rich manganese-based material is within the scope of this application, the obtained lithium-ion battery has a shorter charging time from full discharge to full charge, and a higher pass rate for nail penetration test, which shows that the lithium-ion battery of this application has good nail penetration safety performance while improving the fast charging performance.
[0156] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0157] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0158] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
Claims
1. An electrochemical device, comprising a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector, a first coating and a positive electrode material layer, the first coating being disposed on a surface of the positive electrode current collector, and the positive electrode material layer being disposed on a surface of the first coating away from the positive electrode current collector; The first coating layer includes a first main material, the first main material includes a lithium-rich manganese-based material or a metal oxide, and based on the mass of the first coating layer, the mass percentage of the first main material is 20% to 95%; The diaphragm resistance of the positive electrode plate when the state of charge is greater than 80% is R1Ω, and the diaphragm resistance of the positive electrode plate when the state of charge is 0% to 50% is R2Ω, 100%≤(R1-R2) / R2×100%≤500%.
2. The electrochemical device according to claim 1, wherein: 150%≤(R1-R2) / R2×100%≤480%.
3. The electrochemical device according to claim 1, wherein 0.4≤R1≤80, 0.2≤R2≤13.
4. The electrochemical device according to claim 1, wherein The membrane resistance of the positive electrode sheet when the state of charge is 50% to 100% is R3Ω, 0.3≤R3≤82.
5. The electrochemical device according to claim 1, wherein The lithium-rich manganese-based material includes at least one of lithium nickel cobalt manganese oxide or lithium manganese oxide.
6. The electrochemical device according to claim 1, wherein The metal oxide includes ZnO, and the metal oxide also includes Al element; based on the mass of the metal oxide, the mass percentage of the Al element is 0.6% to 4%.
7. The electrochemical device according to claim 1, wherein: The metal oxide includes TiO2, and a first component is arranged on at least a portion of the surface of the TiO2, wherein the first component includes SnO2, and the first component also includes an Sb element; based on the mass of the metal oxide, the mass percentage of the first component is 44.44% to 55.25%; based on the mass of the first component, the mass percentage of the Sb element is 30.2% to 38.8%.
8. The electrochemical device according to claim 1, wherein The first coating layer further includes inorganic particles, and the inorganic particles include at least one of nano-boehmite or aluminum oxide; based on the mass of the first coating layer, the mass percentage of the inorganic particles is 0% to 77%.
9. The electrochemical device according to claim 1, wherein: The average particle size of the first main material is 160nm to 400nm.
10. The electrochemical device according to claim 9, wherein: The average particle size of the first main material is 200nm to 320nm.
11. The electrochemical device according to claim 1, wherein The first coating layer also includes a first binder, which includes at least one of polyvinylidene fluoride, polyacrylic acid or polymethyl methacrylate; based on the mass of the first coating layer, the mass percentage of the first binder is 3% to 15%.
12. The electrochemical device according to claim 1, wherein The thickness of the first coating layer is 0.2 μm to 2 μm.
13. The electrochemical device according to claim 12, wherein: The first coating layer has a thickness of 1 μm to 1.5 μm.
14. An electronic device comprising the electrochemical device according to any one of claims 1 to 13.
Citation Information
Patent Citations
Charge state interval selection method and device and processor
CN108196191A
Positive electrode plate, secondary battery, and electric apparatus
EP4421898A1
Positive electrode sheet, electrochemical device, and electronic device
WO2024138560A1
Cited By
Electrochemical device and electronic device
WO2026149193A1